Efficiency optimization and analysis of 808nm VCSELs with a full electro-thermal-optical numerical model - Engelhardt, Andreas P.; Kolb, Johanna S.; Roemer, Friedhard; Weichmann, Ulrich; Moench, Holger; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2015)
A high electro-optical conversion efficiency of a VCSEL (Vertical-Cavity Surface-Emitting Lasers) is one of the key requirements for their application in high power systems for heating, illumination and pumping applications. The substantial amount of degrees of freedom in the epitaxial and structural design of a VCSEL demands numerical guidance in form of technology computer aided design (TCAD) modeling for a straight forward and successful optimization of the devices. We set up a full electro-thermal optical model for the simulation of VCSEL devices. The electro-thermal part of the simulation follows a drift-diffusion model complemented by a customized, energy resolved, semi-classical carrier capture theory in the QW regions. Optical modes, eigensolutions of the vectorial electromagnetic wave equation, stem from a finite element vectorial solver. The electro-thermal and optical models are linked via the photon-rate equation using QW gain spectra (screened Hartree-Fock approximation) and iterated to self-consistency in a Gummel-type iteration scheme. For comparison and calibration, experimental reference data was extracted from oxide-confined, top-emitting VCSEL devices with an emission wavelength of 808 nm. Our simulations are in good agreement with the electro-optical characteristics of the experimental reference. With the calibrated, microscopic model, routes of design adjustment for efficiency optimization are explored. Exemplarily, the maximum VCSEL efficiency of the simulated reference design increases by 10% (absolute) when free hole absorption is switched off. Accordingly, with the combination of an electro-thermal and optical description, a balancing of the tradeoffs of pDBR doping towards reduced free carrier absorption results in a noteworthy efficiency improvement which is validated with experimental data.
CRIS-Team Scopus Importer:2021-06-11
Keywords: distributed Bragg reflector; efficiency optimization; electro-thermal-optical; free carrier absorption; high efficiency; semiconductor lasers; VCSEL